PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PENGOLAHAN LIMBAH TERNAK MENJADI ENERGI TERBARUKAN (BIOGAS) DI DESA LA’BO’ - Simon Patabang; Frederik Palallo (Gapenas Publisher, 2022)
La'bo 'Village is one of the villages in North Toraja Regency. It is located about 8 km from the city of Rantepao. The people live as farmers. In addition, generally every household raises livestock in a pen at the back of the house. Manure from each livestock pen is disposed of freely, causing an unhealthy odor around the house. To solve the pollution problem, a training was conducted for the La'bo 'community to build a biogas installation as a tool to properly process livestock manure and provide added value to the community. To build a biogas installation, training is carried out using the on-job training method. The community is invited to work directly to build the installation together so that they can receive the knowledge and skills from this waste treatment technology. The training to build a biogas installation was carried out in collaboration with the Marante Tampang Allo Farmer Group and the Biang Farmer Group. From this training, the community has gained knowledge and skills to build and manage livestock waste into biogas. The result of this collaboration with farmer groups has succeeded in building 2 units of biogas installations with a capacity of 4 m3 of the fixed dome type. With the construction of the biogas installation, the air pollution around the house becomes healthier and the demand for LPG for each household has been replaced by biogas produced from the biogas installation